2018
DOI: 10.1038/s41401-018-0178-4
|View full text |Cite
|
Sign up to set email alerts
|

Influences of an NR1I2 polymorphism on heterogeneous antiplatelet reactivity responses to clopidogrel and clinical outcomes in acute ischemic stroke patients

Abstract: Pregnane X receptor (PXR) is a member of nuclear receptor subfamily 1 (NR1I2) that is a transcriptional regulator of several metabolic enzymes involved in clopidogrel metabolism. In this study we identified and evaluated the contributions of single nucleotide polymorphisms (SNPs) in NR1I2 and cytochrome P450 (CYP) 2C19 alleles to clopidogrel resistance (CR) and long-term clinical outcomes in acute ischemic stroke (IS) patients. A total of 634 patients with acute IS were recruited, who received antiplatelet med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…NR1I2 polymorphisms detected in patients who received cyclosporin (CsA) after their first renal transplantation were correlated with altered CsA C0/D and C2/D after the first month of transplantation, as the haplotype cluster PXR*1B tagged by NR1I2 rs2276707 and rs3814058 was correlated with increased CsA C2/D [77]. A study also indicated the importance of NR1I2 rs13059232 (T > C) as a biomarker for clopidogrel therapy in acute ischemic stroke (IS) patients, since patients carrying the CC genotype exhibited poorer clinical outcome than patients carrying the T allele, while comparable results were not observed in the aspirin cohort [78]. HIVpositive patients treated with atazanavir and ritonavir and carrying the G allele of NR1I2 rs1523130 (T > G) exhibited higher ritonavir intracellular concentrations [79].…”
Section: Discussionmentioning
confidence: 99%
“…NR1I2 polymorphisms detected in patients who received cyclosporin (CsA) after their first renal transplantation were correlated with altered CsA C0/D and C2/D after the first month of transplantation, as the haplotype cluster PXR*1B tagged by NR1I2 rs2276707 and rs3814058 was correlated with increased CsA C2/D [77]. A study also indicated the importance of NR1I2 rs13059232 (T > C) as a biomarker for clopidogrel therapy in acute ischemic stroke (IS) patients, since patients carrying the CC genotype exhibited poorer clinical outcome than patients carrying the T allele, while comparable results were not observed in the aspirin cohort [78]. HIVpositive patients treated with atazanavir and ritonavir and carrying the G allele of NR1I2 rs1523130 (T > G) exhibited higher ritonavir intracellular concentrations [79].…”
Section: Discussionmentioning
confidence: 99%
“…PDW indicates the variability in platelet size, while MPV reflects megakaryocyte and platelet generation. The parameters PDW, PCT, and MPV are markers of thrombopoiesis, wherein a high level of MPV was confirmed to be an independent risk factor of myocardial infarction in patients with coronary heart disease and thus can predict adverse cardiovascular events with high sensitivity[ 15 , 16 ]. Our study revealed that PDW and MPV exhibited a declining trend in the pulmonary heart disease, COPD, and control groups, although PLT and PCT showed an increasing trend.…”
Section: Discussionmentioning
confidence: 99%
“…Three single-nucleotide polymorphisms (SNPs) for CYP2C19 (National Center for Biotechnology Information [NCBI] Genome build 37.1, GenBank NG_008384), including CYP2C19*2 (681G>A, dbSNP rs4244285), CYP2C19*3 (636G>A, dbSNP rs4986893), and CYP2C19*17 (−806C>T, dbSNP rs12248560) [26][27][28][29] , will be genotyped in 3000 participants. Genotyping of the 3 SNPs is performed using the PCR+MassARRAY (flight mass spectrometry).…”
Section: Cyp2c19 Genotyping and 11-dhtxb2 Testingmentioning
confidence: 99%